Quantitative analysis of flavonoid 'naringin' a natural product and its correlation with antioxidant activity in different fruit fractions of grapefruit, citrus decumana Var. Paradisi (macfad.) H.H.A nicholls : Use of industrial waste - DR. BABITA RANA; DR. HARSHAD M. PANDIT (International Journal of Pharma and Bio Sciences, 2017)
Grapefruit [Citrus decumana var. paradisi (Macfad.) H.H.A Nicholls] is a subtropical citrus tree. It is an 18th century hybrid of Citrus maxima × Citrus sinensis, was first bred in Barbados (West Indies). Among the various phytochemicals detected in grapefruit, the flavonoid, naringin, which contributes to the distinctive bitterness of citrus fruits, exerts a variety of pharmacological effects The methanolic extract of different parts of the fruit such as flavedo, albedo, segment membranes and seeds which are the main by products in citrus processing industry were subjected to HPLC analysis for their naringin content with mobile phase containing acetonitrile and 2%acetic acid (25:75) at wavelength 280 nm while antioxidant activity was determined by DPPH free radical scavenging assay. Highest naringin content was detected in albedo, flavedo and juice followed by segment membranes and seeds. Antioxidant activity determined by DPPH free radical scavenging activity revealed the fruit peel containing albedo and flavedo parts with highest antioxidant activity which could be correlated with their flavonoid content.